Towards a more flexible structure of the share capital - A comparison of the company law of South Africa and Switzerland with regard to current debates and developments in the EU - Fuchs Mtwebana, Katja (Department of Commercial Law, 2014)
In this assignment the current legal situation of South Africa and Switzerland with regard to the share capital structure will be examined as well as the movements within both countries towards a more flexible capital structure. This will be followed by a preview on probable future reform steps. Thereby the developments in Switzerland cannot be analyzed completely independent of the developments anticipated within the European Union. Finally a valuation will take place whether South African Company Law can serve as role model for Swiss Company Law and whether the American Revised Model Business Corporation Act still provides the basis for further developments in South Africa.